Gut bacterium Delftia tsuruhatensis strain ALG19 isolated from Agrilus planipennis larvae degrades cellulose in Fraxinus velutina - Wang, Yi-Han; Liu, Qi; Vuong, Thi Minh Dien; Wang, Hua-Ling; Fu, Jing-Yi; Su, Xiao-Yu; Wang, Ying-Jie; Yang, Jia-Yu; Zeng, Jian-Yong; Li, Hui-Ping (Frontiers in Microbiology, 2025)
IntroductionStrain ALG19, a predominant culturable bacterium isolated from the larval gut of the emerald ash borer (Agrilus planipennis) infesting velvet ash (Fraxinus velutina), was investigated to determine its taxonomic identity and evaluate its cellulose-degrading potential.MethodsThe taxonomic classification of ALG19 was determined through whole-genome sequencing, average nucleotide identity (ANI) analysis, and phylogenetic reconstruction based on single-copy orthologous genes. Functional annotation of carbohydrate-active genes was performed using the COG, KEGG, and CAZy databases. Cellulolytic activity was assessed using a multi-faceted approach. First, carboxymethyl cellulose hydrolysis assays were conducted to evaluate cellulolytic capability. Additionally, filter paper degradation and the utilization of velvet ash phloem cellulose were examined. For these experiments, the strain was cultured in an inorganic salt medium supplemented with the respective cellulose substrates for 60 days.ResultsGenomic analyses confirmed that ALG19 belongs to Delftia tsuruhatensis. The strain harbors 283 COG-annotated genes associated with carbohydrate transport and metabolism, 355 KEGG genes involved in carbohydrate metabolism pathways, and 105 CAZy-annotated carbohydrate-active enzymes. Phenotypic assays revealed a carboxymethyl cellulose hydrolysis zone ratio of 1.74. After a 60-day incubation period, ALG19 completely decomposed filter paper strips into flocs, resulting in a 38.06% reduction in dry weight compared to control samples, which basically retained their original shape. Furthermore, the strain degraded velvet ash phloem cellulose, leaving a residual content of 69.91%. This was 15.60% lower than the control, which exhibited a residual content of 82.83%.DiscussionThese findings demonstrate that D. tsuruhatensis ALG19 is capable of degrading cellulose present in the host plant of the emerald ash borer, its associated insect. This study identifies a potential target microorganism for future pest management strategies, which could mitigate the damage caused by the emerald ash borer by impairing its digestive capacity.